OVERCOMING OF UNILATERAL INCOMPATIBILITY OF SWEET PEPPER CV. BELOSNEZHKA AND KARLIK BY COLD STRESS OF POLLEN - E. G. Kozar; O. A. Blandinskaya; L. V. Bespal'ko; N. N. Balashova; V. F. Pivovarov; O. N. Pishnaya (Овощи России, 2015)
The article describes a technique for overcoming the unilateral cross- incompatibility of of sweet pepper cultivars Belosnezhka and Karlik (Capsicum annuumL.) by pre- coating the stigma of the parental plants by own frozen pollen (fertile, but lost fertilizing capacity) in order to initiate the necessary changes in the tissues of the pistil that ensures germination of pollen tubes of foreign pollen , successful fertilization and hybrid seeds formation.